METODE STUDENT FACILITATOR AND EXPLAINING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PENDIDIKAN AGAMA BUDDHA KELAS VIII SMP NEGERI 3 SUNGAILIAT TAHUN PELAJARAN 2021/2022 - Sunarsih, Sunarsih (Jurnal Analisis Pendidikan Sosial, 2024)
This research is entitled Student Facilitator and Explaining Method to Improve Student Learning Outcomes of Buddhist Education Class VIII SMP Negeri 3 Sungailiat Academic Year 2021/2022. This research is an attempt to improve students' ability to speak, communicate and appear in front of their friends more confidently. In the Student Facilitator and Explaining method, students are required to be more active and can create a pleasant learning atmosphere. This research departs from the background of the need for renewal in improving student learning outcomes, because during the last two years during the Covid-19 pandemic, teachers carried out rigid online learning processes, such as the use of Powerpoint and lectures in the virtual learning process. This situation has the potential to cause boredom, boredom and reduce student interest and motivation to learn. The problem in this research is whether the Student Facilitator and Explaining method can improve the learning outcomes of eighth grade Buddhist Education students at SMP Negeri 3 Sungailiat. The method used in this study is the Student Facilitator and Explaining method which aims to improve students' ability to speak, communicate and perform in front of their friends. This research was carried out using a cycle. In the first cycle, some students were not familiar with the conditions of learning the online Student Facilitator and Explaining learning method, so actions were taken by providing explanations and videos of peer exposure to other students. The results of the test in the first cycle, the success of the eighth grade Buddhist religious education students at SMP Negeri 3 Sungailiat changed for the better, so it can be concluded that in this study the Student Facilitator and Explaining method was able to improve student learning outcomes so that they achieved mastery learning.